Corporate governance and initial public offerings : an international perspective - Judge, William Q.; Zattoni, Alessandro (Cambridge, UK ; New York : Cambridge University Press, 2012)
"Initial Public Offerings (IPOs) are unique economic and governance events as privately held firms issue common stock or shares to the public for the first time. The governance issues surrounding IPOs are relatively unexamined compared to more established, and usually larger, firms. As such, they provide a unique context to study corporate governance and its development around the world. Based on a collaborative international research project, this book analyses the corporate governance of IPOs in twenty-one countries, each of which is characterized by different governance environments and different levels of IPO activity. The end result is a broad and deep assessment of governance practices and IPO activity for an array of economies that represent roughly 80 percent of the global economy. These chapters collectively provide new insights into what a global theory of corporate governance might look like and offer guidance to policy makers and academics regarding national governance configurations"-- Provided by publisher
Includes bibliographical references and indexes
Keywords: Corporate governance; Corporations -- Investor relations; Going public (Securities)